Rapid detection of latent fingerprints utilizing fluorescent silica-rhodamine B powder - Abdullah, Sabreen Qahtan; Zageer, Dheaa Shamik; Hussain, Kameran Shukur (Edelweiss Applied Science and Technology, 2024)
Novel S1 and S2 are developed and utilized by integrating rhodamine B with silica gel to detect latent fingerprints (LFPs). The obtained compounds were characterized using XRD, FTIR, and FSEM. The S1 and S2 containing different amounts of rhodamine B (5% for S1 and 10% for S2) with the best photostability are obtained by simple adsorption procedure. When exposed to (365 nm) light, the produced powder emits a bright red fluorescence in its solid state. S1 and S2 are highly effective at detecting fresh and aged latent fingerprints (LFPs) with minimal background interference. This is because the red fluorescence efficiently avoids interference from the substrates’ self-fluorescence. These findings suggest that S1 and S2, with their excellent applicability and reliability, are promising candidates for visualizing LFPs.